تشخيص الكفايات الجوهرية في المنظمات الحكومية "دراسة مقارنة" في مستشفى بغداد التعليمي والشركة العامة لصناعة البطاريات - الطائي علي حسون (Journal of Economics and Administrative Sciences, 2007)
This study Concentrates on modern variable in the human resources management that is Core Competency. The field study is two of Public organizations, The first is Educational Baghdad Hospital, the other is the state Company for Batteries industry, the problem of the study determincs some questions and hypotheses. The data was Collected by questionnaire which Contains six Core Competences leader ship, Communication, frontline execution, development, innovation and self management . The sample contains (26) doctores and (28) heads of departments in the company. The study points out many conclusions, the main of it, there is significant differences among the two organizations. Then the study coneluded with a number of important recommendations serve its objectives.